Nutritional Assessment of Patients After Pylorus-Preserving Gastrectomy for Early Gastric Cancer - Ikeguchi, Masahide (Springer-Verlag, 2010)
The aim of this study was to evaluate the nutritional advantages of pylorus-preserving gastrectomy (PPG) in comparison with distal gastrectomy with Billroth I anastomosis (DG) in early gastric cancer (EGC). Between 2005 and 2007, 24 patients underwent PPG and 30 underwent DG. Subjective global assessment, objective data assessment, and endoscopic findings of the remnant stomach were compared between the two groups. Two years after surgery, the patients’ body weights recovered to 97% in PPG, but they continued to decrease in DG. Postoperative blood lymphocyte counts remained low in DG, but recovered to preoperative levels 6 months after surgery in PPG. Food residue in the gastric remnant was frequently observed in PPG (71.4%) than in DG (15.8%, P = 0.001). In nutritional aspect, PPG may be a more ideal operation than DG. However, food residue in the gastric remnant should be considered in PPG. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12262-010-0167-4) contains supplementary material, which is available to authorized users.